PROPERTIES OF IRON SILICIDES IN SINGLE-CRYSTAL SILICON - Daliev Khojakbar Sultanovich; Khusanov Zafarjon Murodovich (Zeta Repository, 2023)
This paper presents the properties of iron silicide compounds in n-type silicon.